Fabrication of Green PVDF/TiO2 Composite Membrane for Water Treatment - Shuhang Lu; Dong Zou (Membranes)
PVDF/TiO2 composite membranes show some potential to be used for water treatment as they combine the advantages of polymers and ceramics. However, conventional PVDF-based composite membranes are always fabricated by using conventional toxic solvents. Herein, PolarClean was used as a green solvent to fabricate PVDF/TiO2 composite membranes via the phase inversion method. In this process, Pluronic F127 was used as a dispersion agent to distribute TiO2 particles in the PVDF matrix and to serve as a pore former on the membrane surface. TiO2 particles were well distributed on the membrane surface and bulk. TiO2 particles in the PVDF matrix enhanced the mechanical strength and hydrophilic characteristics of the resulting composite membrane, facilitating water transport through the composite membranes and enhancing their water permeability. Membrane microstructures and mechanical strength of the composite membranes were finely tuned by varying the PVDF concentration, TiO2 concentration, and coagulation bath temperature. It was demonstrated that the resulting green PVDF/TiO2 composite membrane showed a high water permeance compared with those using conventional toxic solvents in terms of its small pore size. In addition, the particle rejection of green PVDF/TiO2 membrane showed a 99.9% rejection rate in all the filtration process, while those using NMP showed 91.1% after 30 min of filtration. The water flux was similar at 121 and 130 Lm−2h−1 for green and conventional solvents, respectively. This work provides important information for the future application of sustainable membranes.